2022
DOI: 10.1186/s12866-021-02407-8
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital Microbiota:Potentially Important Determinant of PD-L1 Expression in Male Patients with Non-muscle Invasive Bladder Cancer

Abstract: Background Urogenital microbiota may be associated with the recurrence of bladder cancer, but the underlying mechanism remains unclear. The notion that microbiota can upregulate PD-L1 expression in certain epithelial tumors to promote immune escape has been demonstrated. Thus, we hypothesized that the urogenital microbiota may be involved in the recurrence and progression of non-muscle invasive bladder cancer (NMIBC) by upregulating the PD-L1 expression. To test this hypothesis, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 70 publications
1
21
0
Order By: Relevance
“…Thus, the higher amount of HBD2 induced by the bacteria present in the microbiome impairs the efficacy of BCG therapy [ 16 , 17 , 31 ]. Chen et al demonstrated a significant relationship between the amount of Leptotrichia , Roseomonas , Propionibacterium , Prevotella and Massilia genera in the microbiome of BC tissue and the PD-L1 expression of tumor cells [ 18 ]. Based on the experience of retrospective studies, it was found that the effectiveness of various checkpoint inhibitors was significantly reduced by different antibiotics when used in parallel; this effect may also be explained by distinct changes in microbial composition that are detrimental to therapeutic effectiveness of these anticancer medications [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the higher amount of HBD2 induced by the bacteria present in the microbiome impairs the efficacy of BCG therapy [ 16 , 17 , 31 ]. Chen et al demonstrated a significant relationship between the amount of Leptotrichia , Roseomonas , Propionibacterium , Prevotella and Massilia genera in the microbiome of BC tissue and the PD-L1 expression of tumor cells [ 18 ]. Based on the experience of retrospective studies, it was found that the effectiveness of various checkpoint inhibitors was significantly reduced by different antibiotics when used in parallel; this effect may also be explained by distinct changes in microbial composition that are detrimental to therapeutic effectiveness of these anticancer medications [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al noted the detrimental effect of increased levels of HBD2 on BCG therapy against BC, and later confirmed the exact mechanism of action through Toll-like receptors [ 16 , 17 ]. It is well-known that not only the change in the gut microbiome affects the effectiveness of the anti-tumor checkpoint inhibitors, such as pembrolizumab or nivolumab, but the bacteria present in the urogenital system can also directly inhibit this therapy [ 18 ]. When planning individual therapies, it is essential to have more in-depth knowledge about the components of the bladder tumor microbiome and the HBD levels associated with them.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers generally use urine samples and tissues to study bladder cancer. Despite stools being the most widely used material for other types of studies, urine and tissues are used the most for bladder cancer because of the location of the disease [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Methods For Microbiome Study In Bladder Cancermentioning
confidence: 99%
“…Chen et al [ 43 ] conducted another trial. The authors sought to determine the relationship between PD-L1 expression and microbial abundance.…”
Section: Microbiome Research In Bladder Cancermentioning
confidence: 99%
“…Recently, Chen et al. ( 103 ) explored for the first time the relationship between the microbiota profile and PD-L1 expression in patients with non-muscle-invasive bladder cancer. There were significant differences in the composition of specific bacteria genera between the PD-L1-high group and the PD-L1-low group.…”
Section: Justification Of the Hypothesismentioning
confidence: 99%